THE DEVELOPMENT OF "MAHIR BERBAHASA" LEARNING APPLICATION FOR BIPA STUDENTS OF IKIP BUDI UTOMO MALANG - Munawwir Hadiwijaya; Adi Adi (JURNAL ILMIAH BAHASA DAN SASTRA, 2021)
This research is intended to develop a web-based learning application “Mahir Berbahasa” to support the learning process of BIPA students at IKIP Budi Utomo. The software used in the development of this application is the Codeigniter and Bootstrap Framework. It is hoped that this application will become a student learning medium that can make it easier for foreign students to continue studying wherever they are. This type of research is R&D development research. The development model used is the development of Borg and Gall. The results of this research development product in the form of "Mahir Berbahasa" learning applications have been tested and have received good ratings from users and validators. The assessment includes aspects of visual appearance, aspects of media relevance, aspects of material organization, aspects of software engineering, aspects of effects for learning strategies, and aspects of language. From a value range of 1-5, the user gives a mean value of 4.72, while the validator gives a value of 4.52. Based on this assessment, this learning application is in the category of feasible to use.